Inside Cover Picture: Rhodium(III)‐Catalyzed, CH Activated Annulation to Form Isocoumarins and α‐Pyrones using the ON Bond as an Internal Oxidant (Adv. Synth. Catal. 7/2014). Issue 7 (24th April 2014) - Li, Xing Guang; Liu, Kai; Zou, Gang; Liu, Pei Nian
Abstract : The inside cover picture, provided by Pei Nian Liu and co‐workers, illustrates a mild and regioselective redox‐neutral CH activated annulation protocol for the synthesis of isocoumarins and α ‐pyrones. Without any external oxidant, an ON bond was employed as the internal oxidant in the Rh(III)‐catalyzed annulation. This coupling of benzoates and alkynes is potentially applicable to construct of a broad range of useful O‐heterocycles. Details are reported in the Communication on pages 1496–1500 (X. G. Li, K. Liu, G. Zou, P. N. Liu, Adv. Synth. Catal. 2014, 356, 1496–1500; DOI: 10.1002/adsc.201400200) .